Application of phase change materials to pre-heating of evaporator and pressure regulator of a gaseous sequential injection system - (:unkn) unknown (ELSEVIER SCI LTD, 2011)
The vehicle engines having gaseous sequential injection systems of liquefied petroleum gas (LPG) are operated on gasoline until the engine coolant reaches the required temperature because the heat of the engine coolant passing through the evaporator and pressure regulator (E&PR) is not enough to vaporize the LPG that is at liquid phase. Therefore, the fuel economy and the decreasing pollutant emissions emitted to the environment through use of LPG cannot be completely achieved at cold start of the engines. In this study, an E&PR that can store thermal energy was designed by using of phase change material (PCM) in order to overcome cold start problem of E&PR in vehicles operated with LPG. The thermal behavior of the E&PR with PCM was determined at idle operating conditions and the effects of using the E&PR surrounded with PCM on exhaust emissions (HC, CO) were examined. It was observed from the study that the E&PR with PCM can solve the cold start problem of the LPG powered engines. The E&PR surrounded with PCM could start the engine with LPG after the 15 h cooling period of the engine and LPG usage decreased HC and CO emissions by 17.32% and 28.71%, respectively. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: LPG powered vehicles; Evaporator and pressure regulator of LPG; Thermal energy storage; Phase change materials; Cold start emissions; INTERNAL-COMBUSTION ENGINES; COLD-START; CATALYST; EMISSIONS; BEHAVIOR; PETROL